Language Abstractions for RFID Technology - Lombide Carreton, Andoni; Pinte, Kevin; De Meuter, Wolfgang (Electronic Communications of the EASST, 2009)
Developing pervasive and context-aware applications that make use of RFID technology is a daunting task given the high degree of failures inherent to communication with RFID tags. The reason is that current programming models do not incorporate these failures into the very heart of their computational model. AmbientTalk, a research language aimed at pervasive applications running in mobile ad hoc networks, does offer such a programming model, but it is aimed at mobile devices interconnected via peer-to-peer network connections such as WiFi or Bluetooth. In this paper we show how we use this programming model for the communication with RFID tags.